Our families our future - Weisberg, Roger; Filmakers Library; Public Policy Productions (New York, N.Y. : Filmakers library, 1993)
Walter Cronkite visits six family support programs that focus on prevention, family protection and co-operation to heal America's families
Title from container
Co-producer and co-director, Daniel Klein ; editor, Kathryn Barnier
Hosted by Walter Cronkite
Keywords: Family policy -- United States; Family services -- United States